(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Savchenko K. Yu. Introduction of professional and pedagogical situations as a means of communication skills development among the future pre-school teachers. The article studies possibilities of introducing professional and pedagogical situations as a means of communication skills development among the future pre-school teachers. The existent system of professional training and the work on forming communicative abilities among future teachers need introducing new specially developed pedagogical situations into the educational process of the higher pedagogical schools. These situations should simulate professional activity of a preschool teacher and assist in developing professional competence.